PSYCHOLOGICAL FACTORS OF DEVELOPING ECOPSYCHOLOGICAL CREATIVE ABILITY - Turakulov Buri Norboevich (Bright Mind Publishing, 2025)
This article discusses the motivational methods of developing the ecopsychological creative ability of future primary school teachers, ecopsychological factors of creative thinking, innovative education, issues.
Keywords: Future, primary school, teacher motivation, creative thinking, ecopsychology, ecological culture, innovative education.